Kebijakan Transmigrasi dalam Kerangka Kesejahteraan Sosial dan Ketahanan Nasional di Provinsi Lampung - Susetyo, Heru; Febriyanto, Satrio; Latifah, Tien Tis’aini; Ardiansyah, Deden; Angelina, Feymi; Hamadi, Ibrahim Ghifar; Haq, Najma Izzatul; Fatih, Nurroby (UI Scholars Hub, 2024)
Transmigration in Lampung Province is part of Indonesia's national transmigration program, which aims to equalize development and reduce the population density of densely populated islands such as Java. Transmigration in Lampung began in 1905 with a colonial approach by the Dutch and continued during the Old Order New Order and began to decline after the 1998 reformation. The challenges of transmigration in Lampung include social and economic problems, integration of immigrants with local communities, and environmental impacts; the next challenge is the availability of health and welfare infrastructure and sustainable development. This study examines the dynamics of transmigration in Lampung Province as an instrument of social welfare. The purpose of the study is to describe the development of the transmigration program from the colonial era to the contemporary era, and to identify achievements and challenges in social integration, environmental impacts, and infrastructure development in transmigration areas. The method used is socio-legal, which focuses on studying problems in the implementation of law in everyday society. Data were collected through field studies in Lampung Province in 2024. The findings of this study are that transmigration in Lampung Province has experienced significant development since the start of the program. Lampung Province has shifted from a province receiving transmigration to one that is sending transmigration. Although there have been some socio-economic achievements, challenges remain, especially regarding social integration, environmental impacts, and infrastructure development. The success of the future transmigration program will depend mainly on how these challenges are addressed with a more inclusive and sustainable approach.